Free markets with solidarity and sustainability: Facing the challenge - Schlag, Martin; Mercado, Juan Andrés (Catholic University of America Press, 2016)
The contributors to Free Markets with Sustainability and Solidarity, who represent a unique combination of European and American scholars, present their reflections on evolving forms of economics. All are unified by a holistic, Christian anthropology, from which they draw epistemological consequences for free markets and a free society. ©2016 The Catholic University of America Press. All rights reserved.